Template-free synthesis of hierarchical porous calcium carbonate microspheres for efficient water treatment. Issue 1 (22nd December 2015) - Zhang, Jing; Yao, Bin; Ping, Hang; Fu, Zhengyi; Li, Yu; Wang, Weimin; Wang, Hao; Wang, Yucheng; Zhang, Jinyong; Zhang, Fan
Abstract : Hierarchical porous calcium carbonate microspheres are synthesized by a template-free method, and show potential application in water treatment. Abstract : A uniform, hierarchical porous vaterite calcium carbonate microsphere stacked from nanoparticles is synthesized in dimethylformamide–water (DMF–H2 O) mixed solvent without template. We propose a solvent-reaction assisted synthesis of the product by a mesoscale growth pathway. The product shows large removal capacity towards Pb 2+, Cd 2+ and Zn 2+, of 1960 mg g −1, 1040 mg g −1 and 587.3 mg g −1, respectively. It also exhibits efficient and selective adsorption of Congo red (272 mg g −1, 5 min for equilibrium), which is reported for the first time on calcium carbonate. The removal mechanism is demonstrated to be the precipitation transformation for the heavy metal ion sequestration, and adsorption mechanism for the removal of the organic dyes. The good performance of the product is ascribed to the large amount of active adsorption sites provided by the nanoscale building blocks and mesopores, and the short pathway provided by the sunken poles and the hierarchical structure with enhanced mass transfer and decreased blocking of channels.